Radioimmunoassays of hidden viral antigens. - Neurath, A R (Proc Natl Acad Sci U S A, 1982)
Antigens corresponding to infectious agents may be present in biological specimens only in a cryptic form bound to antibodies and, thus, may elude detection. We describe a solid phase technique for separation of antigens from antibodies. Immune complexes are precipitated from serum by polyethylene glycol, dissociated with NaSCN, and adsorbed onto nitrocellulose or polystyrene supports. Antigens remain topographically separated from antibodies after removal of NaSCN and can be detected with radiolabeled antibodies. Genomes from viruses immobilized on nitrocellulose can be identified by nucleic acid hybridization. Nanogram quantities of sequestered hepatitis B surface and core antigens and picogram amounts of hepatitis B virus DNA were detected. Antibody-bond adenovirus, herpesvirus, and measles virus antigens were discerned by the procedure. IMAGES: